Crocin Alleviates Myocardial Ischemia/Reperfusion-Induced Endoplasmic Reticulum Stress via Regulation of miR-34a/Sirt1/Nrf2 Pathway. Issue 1 (January 2019) - Wang, Xiaowu; Yuan, Binbin; Cheng, Biao; Liu, Ying; Zhang, Ben; Wang, Xianyue; Lin, Xi; Yang, Bo; Gong, Gu
Abstract : ABSTRACT: Endoplasmic reticulum (ER) stress is associated with ischemia/reperfusion (I/R)-induced cardiomyocyte apoptosis. Crocin could protect myocardial cells against I/R injury and suppress ER stress. This study aimed to explore the molecular mechanism of crocin related to ER stress in myocardial I/R injury. We found crocin alleviated I/R-induced cardiomyocyte apoptosis both in I/R-induced primary cardiomyocytes and in mouse models. The expression of Bax, active caspase 3, glucose-regulated protein of 78 kDa (GRP78), and C/EBP homologous protein (CHOP) induced by I/R injury was reduced, whereas Bcl-2 expression was enhanced by crocin, the effect of which was abrogated by ER stress activator thapsigargin treatment. Crocin decreased miR-34a expression, whereas it increased Sirt1, Nrf2, and HO-1 levels, in I/R-induced cardiomyocytes. miR-34a overexpression reduced the expression of Sirt1, Nrf2, and HO-1; in contrast, the suppression of miR-34a upregulated their expression. Sirt1 blocker nicotinamide and Nrf2 siRNA restrained the levels of GRP78, CHOP, Bax, and active caspase 3. The levels of apoptosis- and ER stress-related proteins, and the expression of miR-34a, Sirt1, Nrf2, and HO-1 in I/R-induced mouse models were consistent with those in vitro . In addition, I/R-induced left ventricular dysfunction and infarct were attenuated by crocin in mice. In conclusion, crocin attenuates I/R-induced cardiomyocyte apoptosis via suppressing ER stress, which is regulated by the miR-34a/Sirt1/Nrf2 pathway.